Pengenalan Olahraga Sederhana Bola Keranjang Untuk Meningkatkan Motorik Kasar ABK Tuna Grahita Jenjang SMA di SLB Negeri Pekalongan - Alfira Nuril Aissya Alfira Nuril Aissya (Jurnal Muhammadiyah untuk Olahraga Indonesia, 2023)
Children with special needs are children who have their own uniqueness in their types and characteristics, which distinguish them from normal children in general. So we need a separate stimulant to develop their motor skills. Through this service, the service team tries to introduce some simple sports that can be done together with children with special needs at SLB Negeri Pekalongan. From this service, the SLB students looked very enthusiastic and enthusiastic during the activities. With this, it can be concluded that children with special needs can also participate in activities although they are a little slow in catching understanding, but their enthusiasm for learning something is also very high